Political Economy of Industrial Relations - Hyman, Richard. author. aut Link
XVI, 259 p.
Keywords: This collection of essays attempts to demonstrate how an adequate analysis of trade unions, strikes and collective bargaining must be rooted in a broader understanding of their political and economic context. The second part of the book deals with the central problems of trade unionism.